2023
DOI: 10.1097/md.0000000000033604
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between spasticity and corticospinal/corticoreticular tract status in stroke patients after early stage

Abstract: We investigated the correlation between spasticity and the states of the corticospinal tract (CST) and corticoreticular tract (CRT) in stroke patients after early stage. Thirty-eight stroke patients and 26 healthy control subjects were recruited. The modified Ashworth scale (MAS) scale after the early stage (more than 1 month after onset) was used to determine the spasticity state of the stroke patients. Fractional anisotropy (FA), apparent diffusion coefficient (ADC), fiber number (FN), and ipsilesional/contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Treatment of PSS has largely focused on reducing the area of cerebral ischemia and rescuing neurons from damaged areas of the brain; however, the effects of putative neuroprotectants are less pronounced in clinical trials [ 5 ]. Several recent clinical studies report that the degree of corticospinal tract (CST) damage correlates with the severity of spasticity in patients with chronic stroke [ 6 – 8 ] and that there is a significant correlation between motor function improvement and CST remodeling in patients with PSS [ 9 ]. A few experimental studies have also observed that by destroying the corresponding CST, the upper motor neurons lose control of the spinal cord, causing spasticity of the contralateral limb [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of PSS has largely focused on reducing the area of cerebral ischemia and rescuing neurons from damaged areas of the brain; however, the effects of putative neuroprotectants are less pronounced in clinical trials [ 5 ]. Several recent clinical studies report that the degree of corticospinal tract (CST) damage correlates with the severity of spasticity in patients with chronic stroke [ 6 – 8 ] and that there is a significant correlation between motor function improvement and CST remodeling in patients with PSS [ 9 ]. A few experimental studies have also observed that by destroying the corresponding CST, the upper motor neurons lose control of the spinal cord, causing spasticity of the contralateral limb [ 10 ].…”
Section: Introductionmentioning
confidence: 99%